PROSPEK PROGRAM STUDI AGAMA DAN UMUM DI STA IN PONTIANAK, KALIMANTA N BARAT , DAN STA IN CURUP BENGKULU - Nurudin Nurudin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
The tendency of an Islamic university to open general subject faculties or program can be seen from the process of transformation and institutional change of the university. STAINs that are mandated to develop Islamic study are experiencing dilemma between following the trend of people need and being consistent with developing Islamic teaching. This study discusses about STAIN Pontianak that develops religious study programs and STAIN Curup that develops general study programs. This study uses qualitative descriptive method and shows that religious study programs in STAIN Pontianak can be developed due to its ability while general courses in STAIN Curup is popular as marked by the increasing number of graduates of general courses and high absorption in the formal sector. Challenge in the development of flagship study programs in STAIN is the parallel between Islamic values and general competence as the requirement of the region. The government is required to provide certainty in the development of study program in STAINs to actualize the development of excellent and competitive study program.